USDA review of the informal EU Council meeting to launch its ‘hearts and minds' campaign - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
EU ministers have reviewed the outcome of the Cancun WTO Ministerial and agreed...